The genetic basis of late blight resistance in potato: A comprehensive overview - Tarabain, G.; Lindqvist-Kreuze, H.; Gravel, V.; Stromvik, M.V. (2025)
Potato late blight, caused by the oomycete Phytophthora infestans (Mont.) de Bary, is a global problem causing economic losses and threatening food security. Fungicide application is the traditional control method, though it is costly and harmful to the environment, and P. infestans rapidly develop fungicide resistance. Thus, breeding resistant potato varieties remain the most sustainable approach to disease management. Resistance (R) genes derived from wild Solanum species have been widely used in breeding programs, though P. infestans frequently overcomes single-gene resistance through effector evolution. While significant progress has been made in identifying resistance determinants, the molecular and evolutionary dynamics governing potato-P. infestans interactions are yet to be fully understood, limiting efforts to achieve durably resistant varieties. Recent studies aided by increasing amounts of genomics data have uncovered novel immune components, such as the PERU receptor and epidermal chloroplast immune components, offering new insights into plant immunity and potential disease management. This review summarizes the genetic factors contributing to late blight resistance in potatoes and the innovative breeding strategies to meet the challenges of this persistent agricultural disease.